Long-Term Improvement of Gait Kinematics in Young Children with Cerebral Palsy Treated with Botulinum Toxin Injections and Integrated/Intensive Rehabilitation: A 5-Year Retrospective Observational Study - Weronika Pyrzanowska; Magdalena Chrościńska-Krawczyk; Marcin Bonikowski (Toxins)
Introduction: Patients with cerebral palsy (CP) present mobility limitations that alter their activity and participation in social life. This study aimed to assess changes in gait kinematic measurements using the Observational Gait Scale (OGS) and preselected parameters related to the foot, knee, and hip in children with CP who received repeated BoNT-A injections within a rehabilitation treatment over a five-year follow-up period. Material and methods: This single-center retrospective observational study included 200 consecutive children with bilateral CP (GMFCS I–IV). The five-year follow-up period was analyzed. Patients received between 5 and 10 BoNT-A treatments (mean 7.6 ± 2.3), with total doses per session varying from 20 units/kg to 30 units/kg for ABOBoNT-A and from 10 units/kg to 20 units/kg for OnaBoNT-A. In most cases, multilevel injections were performed, including in the hip flexors and adductors, knee flexors, and foot plantar flexors. Results: The mean age of the patients at the beginning was 32.23 months (±6.96). The OGS score improved in 74.5% and 76.5% of the patients, and deterioration occurred in 8.5% and 7% of patients for the right and left lower extremities, respectively. The changes in the OGS typically ranged from 1 to 4 points. Significant improvements in the knee position at midstance, initial foot contact, foot contact at midstance, timing of heel rise, and knee and hip positions at terminal stance were observed. Conclusions: The data from our retrospective observational study show a significant, long-term, positive effect of integrated treatment on gait kinematics in patients with CP in a homogenous group of young children with bilateral spastic cerebral palsy.